Pemanfaatan Kacang Hijau untuk Produksi Bakpia sebagai Upaya Edukasi Gizi dan Pencegahan Stunting di Desa Hutadaa Kecamatan Telaga Jaya Kabupaten Gorontalo - Hapsawati Taan; Rahmatiah; Nuryana Fadila; Astika Firdasari; Fitriani Malatia; Saskia Aulia Gani; Nidaurrahmah Usman; Taufik Hidayat; Rifki Suaib9; Yusuf Karim (Jurnal Ragam Pengabdian, 2025)
This community service aims to empower the residents of Hutadaa Village through training in the production of mung bean bakpia as a healthy snack alternative to support stunting prevention. This activity is an implementation of the Tri Dharma of Higher Education, encompassing education, research, and community service. Considering the high prevalence of stunting in Indonesia, the program seeks to increase community awareness about nutritious food consumption and encourage economic independence based on local agro-industry. The results showed high participant enthusiasm, improvement in technical skills, and the emergence of community initiatives to optimize the potential of mung beans.